RANCANG BANGUN SISTEM INFORMASI MONITORING PELANGGARAN TATA TERTIB SISWA BERBASIS WEB - Safitri, Widia; Sarmidi; Habibie, Alfadl (Program Studi Pendidikan Teknologi Informasi, 2024)
This study aims to design and develop a web-based student discipline violation monitoring information system at SMK Islam Kawalu, as well as evaluate its feasibility. The research uses the Research and Development (R&D) method with the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The design is carried out using Unified Modeling Language (UML), and the system is developed using PHP programming language. The results show that the system is deemed